A conceptual model of digital banking adoption intention in Malaysia: Integrating TAM and TPB - Muhamad, Mahathir; Ismail , Mohammad; Muhayiddin , Mohd Nazri; Abdullah , Ahmad Ridhuwan; Mat Yunoh, Muhammad Naqib; Mat Hassan, Abd Aziz (International Journal of Accounting, Finance and Business, 2026)
The rapid advancement of financial technology has transformed the global banking landscape, leading to the emergence of digital-only banking services and platform-based financial ecosystems (Barroso & Laborda, 2022; Verhoef et al., 2021). In Malaysia, despite strong regulatory support and high digital infrastructure readiness, consumer adoption of digital banking remains uneven (Bank Negara Malaysia, 2022). This conceptual paper aims to develop an integrated theoretical framework to explain behavioural intention to adopt digital banking services by synthesising the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) (Ajzen, 1991). The proposed framework incorporates perceived ease of use, perceived usefulness, trust and subjective norm. By integrating technological, psychological, and social determinants, this study advances fintech adoption literature and offers a comprehensive perspective on digital banking adoption in emerging economies.